SIMULATION STUDY ON THE MAIN INFLUENCE FACTORS OF THE SURFACE SCALE-TEXTURE OF COLD ROLL-BEATING FORMING PARTS - LIANG XiaoMing; LI Yan; YANG MingShun; YUAN QiLong; WU XueLiang; FENG JingMin; LI Long (Jixie qiangdu, 2017)
Aiming at flaws of scale-texture on the surface of cold-roll beating forming parts,according to the basic principles of cold-rolling beating forming,analyzes the main reasons and affecting factors of scale-texture flaws is carried out. The simulation model is built by using the simulation software of ABAQUS. The change law of scale-texture height and width were simulated under the way of forward beating and backward beating,and when rolling wheel speed change and the work-piece bottom surface along the positive direction. The height and width of scale-texture and section shape were simulated under the way of forward beating and backward beating. Forming experiment is conducted on the refitted cold roll-beating forming equipment,the height of scale-texture and 2D section shape is obtained by scale-texture measurement on the surface of cold roll-beating forming parts,the validity of finite element simulation model is verified by intercomparison of experimental results and 2D section shape,so as to provide reference for surface quality control and selection of parameters parameters